PASSENGER MANIFEST DATA MANAGEMENT ANALYSIS ON IMMIGRATION EXAMINATION ON THE IMMIGRATION CROSSING APPLICATION (APK) AT IMMIGRATION EXAMINATION AT HUSEIN SASTRANEGARA INTERNATIONAL AIRPORT - Rizky Andarujati (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
The existence of the system used by humans over time will experience problems or problems and increase the system requirements needed by system users. One of the applications of SIMKIM at the Air Immigration Checkpoint (TPI) is the Immigration Crossing Application (APK) system. This APK is a transformation of the Border Control Management (BCM) system which has the function of capturing, verifying, matching, and recording data contained in electronic travel documents, namely passports and other travel documents such as visas, travel document readers, biographical & biometric identities, watch lists , automatic border control. If the airline passenger manifest has been integrated with the APK system, the immigration check can be more efficient in terms of how much input is made to produce maximum output, the application of which can be a comparison of the inputs carried out in the immigration inspection process using an integrated APK system to get maximum output in the form of fast immigration checks and accurate data because it is supported by the passenger manifest data.